Correlation between severity of erosive reflux esophagitis and its manometric findings in a tertiary hospital at East Coast, Peninsular Malaysia - Mahno, Noor Ezmas; T, Sahrol Azmi; Mohammad Amjad, Nasser; Kasian, Junaini (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2015)
The burden of Gastroesophageal Reflux Disease, GERD in Asia-Pacific region is increasing. Objectives: To evaluate the manometric finding in erosive reflux esophagitis and its correlation with severity among patients who were seen at Surgical Department, Hospital Tengku Ampuan Afzan (HTAA), Kuantan. Methodology: This was a cross sectional study which involved 60 patients seen from September 2012 until January 2014. Patients were required to fill up the Reflux Disease Specific Questionaire and subsequently underwent manometric evaluation. Descriptive statistics and Pearson’s correlation were applied using SPSS version 18.0. Results: There was no correlation between the severity of Erosive Reflux Disease with the Lower Esophageal Sphincter Pressure or esophageal motility. There was positive correlation (r = + 0.54) between severity of Erosive Reflux Disease and velocity variables of esophageal motility but it was not statistically significant. Discussion: Few experts opined that Erosive Reflux Disease is associated with esophageal dysmotility but there was no specific pattern of esophageal mean wave amplitude in our study sample. The limitation of this study was the sample’s selection and size. Thus, we need further study with better methodology and sample size. Conclusion: In conclusion, there was no significant correlation between the severity of Erosive Reflux Esophagitis on the Lower Esophageal Sphincter pressure and the esophageal motility